FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN KANKER SERVIKS DI RSUD Dr. M. YUNUS BENGKULU TAHUN 2011 - Maryani, Dili; Wahyuni, Elly; Sumiati, Sri (Politeknik Kesehatan Kemenkes Bengkulu, 2012)
Cervical cancer is the second deadly disease to the women Dr. M.Yunus hospital recorded 25 cervical cancer cases in 2009, recorded 30 cervical cancer cases in 2010 then increased up to 40 cases in2011. The objective of this research is to recognize in factors which influenee cervical cancer cases in Dr. M.Yunus Hospital in Bengkulu, in 2011.The research was held since July 2012, 2012 to August 12, 2012. The population of this research were all the fertile age women who came to midwifery polyclinic of Dr. M.Yunus hospital in Bengkulu, in 2011. With amount 0f 3.609 patient but only 40 woman who got cervical cancer. The sampling was takes with the comparison 1:1 that is forty cases total sampling and forty control taken systematically random sampling and case control is used in this research. The data used is secondary data and analized by univariat and bivariat with T-test.Based on the research we found that the average age of fertile women is 43.83 years old, the average age of marriage is 21.53 years old. The maternal parity rate is 2,61. There is not any difference of age to the cervical cancer cases. There is small difference between the age, of marriage and parity towards cervical cancer in Dr. M. Yunus hospital in Bengkulu in 2011. There is no correlation between hormonal contraception user and cervical cancer case in Dr. M. Yunus hospital.Midwives should improve their knowledge and the society understandings about cervical cancer through seminar.